Carbon pricing and competitiveness: are they at odds?. (20th October 2020) - Venmans, Frank; Ellis, Jane; Nachtigall, Daniel
ABSTRACT: This paper reviews ex-post empirical assessments on the impact of carbon pricing on competitiveness in OECD and G20 countries, primarily in the European Union, in the electricity and industrial sectors. Most of these assessments find no statistically significant effects of carbon pricing or energy prices on different dimensions of competitiveness, including net imports, foreign direct investments, turnover, value added, employment, profits, productivity, and innovation. When statistically significant results have been found, the magnitude of such effects tends to be small – either positive or negative. Thus, concerns about negative short-term effects of carbon pricing on firms' or sectors' international competitiveness have not come to pass, at least to date. These findings are in part because carbon price levels have been low and because of exemptions to carbon taxes for industry, or generous levels of free allowances to firms covered by emissions trading schemes. Key policy insights Most of the studies reviewed in this paper find no statistically significant effects of carbon pricing or energy price fluctuations on different dimensions of competitiveness (employment, profits, net imports). When statistically significant results have been found, the magnitude of such effects is small. This is not surprising, because long term trends in overall energy costs have a small effect compared to other trends. Moreover, carbon costs levied on industry have been low, either because of carbon tax breaks or free allowances to firms. Carbon pricing has a small and positive effect on productivity and innovation. In particular, all studies report statistically significant increases in patenting. Studies that find small negative competitiveness effects tend to focus on net imports and outward foreign direct investment. Establishing a positive and stable carbon price (even if initially at a low level) will provide a clear signal of policy direction for participating firms. This may actually reduce risks to competitiveness in the longer-term if it incentivises firms to adopt advanced pollution abatement technologies in an increasingly carbon-constrained global economy.